Analysis of the Effects of the COVID-19 Pandemic on Coffee Agribusiness: A Case Study of a Farm in Triângulo Mineiro, Brazil - Leal, Tamira Alessandra Barbosa; Duarte, Sérgio Lemos; Duarte, Denize Lemos; Fehr, Lara Cristina Francisco de Almeida (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2024)
Coffee is one of the most traded commodities in agribusiness, with Brazil being the largest producer and exporter of the bean. In this context, its cultivation has been widely explored in the field of management studies, since it is vulnerable to externalities and contingency factors, such as the Covid-19 pandemic. The present research aimed to identify the main effects caused by the Covid-19 pandemic on costs, price and management process in coffee farming. Using a mixed approach, applied nature and descriptive objectives, a case study was carried out on a coffee producing farm in the Triângulo Mineiro region. A semi-structured interview was conducted with the property manager, on-site observation and statistical tests on the property's production cost data from the 2016 to 2021 harvests were performed. As a result, a significant effect of the pandemic was observed on aspects of cost, price and management of coffee farming. Pesticides and fertilizers were the most affected items, as well as expenses on machinery, parts and maintenance, and diesel oil. It was then possible to infer the strong relationship of agribusiness with the international market, since the most impacted cost variables were those quoted in dollars or negotiated outside the country, as well as the selling price of coffee itself. In response to the contingencies, the manager had strategies to maintain profitable activity. The research is justified by the lack of related studies, the relevance of coffee farming to the national economy, and the opportunity to help producers anticipate the contingencies related to this research.